1999
DOI: 10.1191/096120399678847632
|View full text |Cite
|
Sign up to set email alerts
|

Chilblain lupus erythematosus is associated with antibodies to SSA/Ro

Abstract: Chilblain lupus erythematosus (CL) of Hutchinson is a subtype of lupus erythematosus (LE) characterized by erythematous lesions induced by cold, damp climates. A number of patients affected by CL eventually develop features of systemic lupus erythematosus (SLE). We report here 9 patients with chilblain cutaneous lesions, 6 of them were affected by SLE and 2 by SCLE. The onset of CL preceded the diagnosis of LE, from 1 to 10 years in 3 cases, it was concurrent in one case and was subsequent in the remaining 4 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 15 publications
1
8
1
1
Order By: Relevance
“…Pathological features are similar to those observed in DLE. Contrary to the results of Franceschini et al, 32 there was no association in this study between chilblain lupus and the presence of anti-Ro/SSA antibodies.…”
Section: Discussioncontrasting
confidence: 86%
“…Pathological features are similar to those observed in DLE. Contrary to the results of Franceschini et al, 32 there was no association in this study between chilblain lupus and the presence of anti-Ro/SSA antibodies.…”
Section: Discussioncontrasting
confidence: 86%
“…Anti-Ro/SsA and antiphospholipid antibodies have also been found to be positive in a few studies. [ 7 ] Su et al .,[ 8 ] proposed the Mayo Clinic Diagnostic criteria for a confirmative diagnosis of CHLE. Major criteria include skin lesions in acral locations induced by exposure to cold or a drop in temperature, and evidence of lupus erythematosus in the skin lesions by histopathologic examination or DIF.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also reported higher frequency of nailfold bleeding in SLE patients than in normal subjects. 22,29 Andrade et al 3 inferred that the occurrence of micropetechiae of focal distribution was related to everyday microtrauma that may occur in healthy individuals. They also stated that because it is a dynamic phenomenon, agreement may be low in two consecutive readings (72%) with variable intervals from weeks to months.…”
Section: Resultsmentioning
confidence: 99%